Exploring Fathers’ Educational Media Needs During the Maternal-Perinatal Period in Yogyakarta - Warsiti Warsiti; Andari Wuri Astuti; Herlin Fitriani Kurniawati; Hari Akbar Sugiantoro; Kriska Afri Juliandari; Sesaria Lukman (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2025)
Introduction: In this study, we aimed to identify the needs for interactive educational media to optimize fathers’ involvement during the maternal-perinatal period in Yogyakarta. With evidence showing that paternal engagement contributes significantly to maternal well-being, child development, and family health outcomes, our objective was to explore the specific barriers and preferences of expectant fathers to address gaps in current health education strategies that remain largely mother-centered. Methods: This qualitative study employed focus group discussions with midwives and in-depth interviews with expectant fathers and mothers at public health centers in Yogyakarta (July–August 2025). Participants (6 midwives, 10 fathers, 10 mothers) were purposively recruited to ensure variation in socioeconomic and educational backgrounds. Data collection proceeded until thematic saturation was achieved. Transcripts were coded inductively and analyzed thematically using NVivo, applying constant comparison across cases. Credibility was enhanced through iterative refinement of codes. Ethical clearance was obtained from the Health Research Ethics Committee of UNISA Yogyakarta (Ref No.4601/KEP-UNISA/VI/2025); all participants gave written informed consent. Results: The primary outcome was the identification of fathers’ educational needs during the maternal-perinatal period. Four themes emerged from data analysis and revealed; limited access to practical; father-focused learning resources; cultural barriers due to patriarchal norms; and a strong preference for interactive and technology-based media such as mobile applications, simulations, and audiovisual content Conclusion: This study underscores the need for father-focused, context-specific educational media. Findings suggest incorporating mobile-based modules featuring short videos, simulations, gamified content, and blended online-offline practice. Such designs can possibly strengthen paternal confidence and engagement, enhancing maternal well-being and infant outcomes while informing innovative perinatal health promotion strategies in similar contexts.